2011
DOI: 10.1007/jhep02(2011)030
|View full text |Cite
|
Sign up to set email alerts
|

Closed flux tubes and their string description in D =3+1 SU(N) gauge theories

Abstract: Abstract:We calculate the energy spectrum of a confining flux tube that is closed around a spatial torus, as a function of its length l. We do so for various SU(N ) gauge theories in 3+1 dimensions, and for various values of spin, parity and longitudinal momentum. We are able to present usefully accurate results for about 20 of the lightest such states, for a range of l that begins close to the (finite volume) deconfining phase transition at l √ σ ∼ 1.6, and extends up to l √ σ ∼ 6 (where σ is the string tensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
260
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(282 citation statements)
references
References 49 publications
20
260
2
Order By: Relevance
“…These flux tubes are stabilised by being wound around a spatial torus and we calculate the energies of the lightest few eigenstates as a function of the flux tube length l, for various quantum numbers. This work greatly extends and supersedes that published in our earlier brief letter [1], and is part of a larger project which has included the calculation of the spectrum in D = 3 + 1 [2], as well as the spectrum and string tensions [3,4] of flux tubes with flux in some higher representations, e.g. k-strings.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…These flux tubes are stabilised by being wound around a spatial torus and we calculate the energies of the lightest few eigenstates as a function of the flux tube length l, for various quantum numbers. This work greatly extends and supersedes that published in our earlier brief letter [1], and is part of a larger project which has included the calculation of the spectrum in D = 3 + 1 [2], as well as the spectrum and string tensions [3,4] of flux tubes with flux in some higher representations, e.g. k-strings.…”
Section: Introductionsupporting
confidence: 62%
“…We have kept the discussion in this paper relatively brief, since most of the relevant issues are discussed at greater length in our recent paper on the flux tube spectrum in D = 3 + 1 [2] and in a recent set of lectures by one of the authors [9], to which we refer the interested reader.…”
Section: Jhep05(2011)042mentioning
confidence: 99%
“…In fact, on the lattice it is also possible to accurately study the corrections to the linear dependence of the torelon energy, which become non-negligible at intermediate values of the torelon length L. This issue has been addressed in many studies [12,16,[109][110][111][112][113][114][115][116][117], including also for flux tubes in higher representations, or for excited string states. The results indicate that the leading correction to the linear dependence of m on L can be expressed in terms of a "Lüscher term", due to the quantum fluctuations of the torelon [118],…”
Section: Lattice Results For Large-n Gauge Theories In (3 + 1) Spacetmentioning
confidence: 99%
“…[115], can be accurately compared with the predictions from an effective Nambu-Gotō string model. theories is also confirmed by some recent, high-precision studies of excited string states, like those reported in ref.…”
Section: Lattice Results For Large-n Gauge Theories In (3 + 1) Spacetmentioning
confidence: 99%
See 1 more Smart Citation